A ladder-truss of citizen participation: re-imagining Arnstein's ladder to bridge between the community and sustainable urban design outcomes. (21st February 2022) - White, Marcus; Langenheim, Nano
There are well understood urban design approaches that respond to the economic, social, and environmental pillars of sustainable development, but urban design decision-making for sustainable outcomes is complex both technically and, in democratic societies, politically. Urban design decision-making must incorporate citizen participatory processes that, as Sherry Arnstein in her 1969 paper, 'A ladder of citizen participation' points out, are undertaken at varying levels ranging from the tokenistic through to citizen control. In this paper, we explore benefits and challenges of citizen participatory processes illustrated with practical examples from an Australian context and propose improvements that utilise emerging technology. We then outline a new approach that rotates Arnstein's ladder diagram 90° to instead form a ladder-truss of citizen participation. This ladder-truss includes aspects of each rung as a structurally necessary and interwoven component of inclusive participation aimed at bridging between the community and sustainable urban design outcomes.